480 Cerebrospinal Fluid Volume Assessed From Clinical T1w-MRI Predicts Functional Outcomes Post-Thrombectomy. (April 2023) - Shamulzai, Ahmad; Kawas, Mohammad; Kittel, Carol; Curry, Brian Patrick; Kim, Jeongchul; Atcheson, Kyle; Whitlow, Christopher; Wolfe, Stacey Q.
Abstract : INTRODUCTION: Endovascular treatment (EVT) is recognized as the standard of care for patients with acute ischemic stroke caused by large vessel occlusion (LVO). However, many patients do not achieve functional independence after successful EVT, which may be due to the pre-existing brain atrophy and higher total cerebrospinal fluid volume (CSFV). Prediction of patients who will highly benefit from EVT may be possible using baseline total CSFV as a marker of brain health and reserve. METHODS: We performed a retrospective analysis of Wake Forest Baptist Health's Stroke Thrombectomy and Aneurysm Registry (n = 602), collected between 2015 - 2021. We selected 213 patients (mean age 67.5 ± 14.6, 49.3% female) who had adequate MRI within 14 days of EVT and a record of the modified Rankin scale (mRS) at 90 days post EVT. Clinical T1w images were transformed into high-resolution images using the convolutional neural network SynthSR. Then, FreeSurfer was used to estimate total cranial CSFV including the ventricles and choroid plexus. To correct for head size, total CSFV was adjusted to the estimated total intracranial volume. RESULTS: Baseline total CSFV significantly predicted 90-day mRS in an ordinal regression model adjusted for baseline mRS (p < 0.001). After further adjustment for age, sex, smoking history, prior stroke, hypertension, congestive heart failure, hemoglobin A1c, atrial fibrillation, ASPECT score, and other confounders, total CSFV remained an independent predictor of 90-day mRS (p = 0.007). CONCLUSIONS: This study elucidates the clinical implications of pre-existing brain health and reserve in the setting of acute ischemic strokes to aid clinicians in treatment decisions impacting prognosis. Increased total CSFV correlates with increased brain frailty and poorer functional outcomes after mechanical thrombectomy, which may ultimately attenuate its benefit.